The Emerging Role of β-Lactams in the Treatment of Methicillin-Resistant Staphylococcus aureus Bloodstream Infections - Molina, Kyle C.; Morrisette, Taylor; Miller, Matthew A.; Huang, Vanthida; Fish, Douglas N. (Antimicrobial agents and chemotherapy, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections (BSI) are associated with substantial morbidity and mortality. Monotherapy with first-line antimicrobials such as vancomycin (VAN; glycopeptide) and daptomycin (DAP; lipopeptide) are inadequate in some cases due to reduced antibiotic susceptibilities or therapeutic failure. In recent years, β-lactam antibiotics have emerged as a potential option for combination therapy with VAN and DAP that may meet an unmet therapeutic need for MRSA BSI. Methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections (BSI) are associated with substantial morbidity and mortality. Monotherapy with first-line antimicrobials such as vancomycin (VAN; glycopeptide) and daptomycin (DAP; lipopeptide) are inadequate in some cases due to reduced antibiotic susceptibilities or therapeutic failure. In recent years, β-lactam antibiotics have emerged as a potential option for combination therapy with VAN and DAP that may meet an unmet therapeutic need for MRSA BSI. Ceftaroline (CPT), the only commercially available β-lactam in the United States with intrinsic in vitro activity against MRSA, has been increasingly studied in the setting of VAN and DAP failures. Novel combinations of first-line agents (VAN and DAP) with β-lactams have been the subject of many recent investigations due to in vitro findings such as the “seesaw effect,” where β-lactam susceptibility may be improved in the presence of decreased glycopeptide and lipopeptide susceptibility. The combination of CPT and DAP, in particular, has become the focus of many scientific evaluations, due to intrinsic anti-MRSA activities and potent in vitro synergistic activity against various MRSA strains. This article reviews the available literature describing these innovative therapeutic approaches for MRSA BSI, focusing on preclinical and clinical studies, and evaluates the potential benefits and limitations of each strategy.